Association between work-family conflict and depressive symptoms in female workers: An exploration of potential moderators. (July 2022) - Lee, Jiseung; Lim, Ji-Eun; Cho, Song Heui; Won, Eunsoo; Jeong, Hyun-Ghang; Lee, Moon-Soo; Ko, Young-Hoon; Han, Changsu; Ham, Byung-Joo; Han, Kyu-Man
Abstract: Work-family conflict (WFC), an inter-role conflict between work and family, negatively affects mental health. Using a nationally representative systematic sample, this study aimed to investigate the association between WFC, depressive symptoms, and potential moderators in the association of adult female workers. Data of 4714 female workers (aged ≥19 years) were obtained cross-sectionally from the 2018 nationwide Korean Longitudinal Survey of Women and Families (KLoWF). WFC was assessed using a 7-item questionnaire, based on which scores were classified into high (>75th percentile score) and low (≤75th percentile score) levels of WFC. Significant depressive symptoms were defined as a score of ≥10 on the 10-item version of the Center for Epidemiologic Studies for Depression Scale. Female workers with high WFC levels were more likely to have depressive symptoms than those with low WFC levels (odds ratio = 2.29, 95% confidence interval = 1.91–2.74). In stratified analyses, high WFC levels were associated with the highest odds of depressive symptoms in the following groups: young adults (19–39 years), those with a college degree or above or with high income, never-married individuals, those with a family size of three or a single child, nonstandard workers, and pink-collar workers. This study replicated and extended previous findings on the association between WFC and depressive symptoms. The association was moderated by age, education and income levels, marital status, family size, number of children, and job conditions. Highlights: The association between work-family conflict (WFC) and depression was investigated. Data of 4714 female workers (aged ≥19 years) in the KLoWF were used. High level of WFC were associated with higher odds for depression. Early adults and never-married women showed stronger association. Socioeconomic status, family structure, and job conditions moderated the association.